(untitled) (Revista Científica Estelí, 2016)
This research develops a technology for processing dehydrated bean powder. This research has a mixed approach, quantitative and qualitative. A survey covering skills of acceptance, product presentations preference, purchase frequency, consumer demographics and competition was applied. A univariate analysis of five repetitions of the process flow obtained in Phase 3 was conducted to evaluate the mass balance of the prototype, in the different steps of the flow of final process: soaking, cooking, grinding, dehydrated, dry grinding, and final prototype. The main results show that the yield of raw beans to the final dehydrated product is rehydrated 40.72 % and increases to 181%, demonstrating that there is no loss of the product by applying dehydration technology. The research exposes product acceptance in the market, 90% of respondents being willing to consume dried beans. 90% of stakeholders, 60% occasionally buy the product and 40% frequently. 80 % of respondents liked the taste of the beans, 15% would improve their consistency, 3% will increase the salt concentration , and 2% improve texture. Keywords: Technology, bean, processing.